Analysing Authenticity: Explaining What it is to be True to Yourself and Why this is Good - Mogomotsi, Olerato Kau (Department of Philosophy, 2021)
My project is a conceptual analysis of authenticity that seeks to achieve reflective equilibrium with our considered judgments about authenticity. Given that we ordinarily take authenticity to mean “being true to oneself” and to generally be a good thing, I develop a philosophical conception of authenticity that can adequately account for the following questions: “What is it that we are being true to?”, “What does being true to oneself entail?” and “What is good about being authentic?” I take particular interest in Aristotelianism virtue Eudaimonism and how it can help in providing a tenable understanding of what authenticity is. In answering the first question, I seek to develop a modified account of Alasdair's MacIntyre's (1981) narrative unity of the self, which I term the Extrapolated Narrative Unity of Self [ENUS], as a tenable understanding of the self which we are being true to when being authentic. The ENUS, in short, is a configured narrative unity of self that combines an individual's actual past and present with their projected future self where the projected future self is a function of their telos. Thereafter, I will take being true to ones ENUS to be laden in the effort and wholesome commitment required for one to put into configuring, expressing, maintaining and reasserting the self. Finally, I argue that we ordinarily understand authenticity to be good because we generally take it to require and reinforce a virtuous life for the individual who is authentic. In addition, I argue that we generally understand authenticity to be good because of its inextricable link to a characteristically Eudaimonic life.